14
$\begingroup$

Accidentally while trying to evaluate a similar integral, I think originally found here, I have taken the denominator instead of $x^4+4x^2+1$ as $x^4+x^2+1$ and stumbled into the following integral: $$J=\int_0^\infty \frac{(x^2-1)\arctan(x^2)}{x^4+x^2+1}dx$$ I think this have a closed form because the linked one has a simple closed form: $\displaystyle{\frac{\pi^2}{12\sqrt{2}}}$, also if there is $\arctan x $ instead of $\arctan(x^2) $ then we have: $$\int_0^\infty \frac{\arctan x}{x^4+x^2+1}dx=\frac{\pi^2}{8\sqrt{3}}-\frac{2}{3}G+\frac{\pi}{12}\ln(2+\sqrt{3})$$

Some proofs are found here: Using $\int_0^{\infty} \frac{\tan^{-1}(x^2)}{x^2+a^2} \ dx$ or using residues. Anyway I started by splitting into two integrals and substituting $x=\frac{1}{t}$: $$\int_0^\infty \frac{x^2\arctan(x^2)}{x^4+x^2+1}dx=\int_0^\infty \frac{\frac{\pi}{2}-\arctan\left(x^2\right)}{x^4+x^2+1}dx\Rightarrow J=\frac{\pi^2}{4\sqrt{3}}-2\int_0^\infty \frac{\arctan(x^2)}{x^4+x^2+1}dx$$ Well, now the main issue is to evaluate: $\displaystyle{I=\int_0^\infty \frac{\arctan(x^2)}{x^4+x^2+1}dx}$

Using the same method as in the second link I arrived at: $$I=\left(\frac{1-i\sqrt 3}{2}\right)f\left(\sqrt{\frac{1+i\sqrt 3}{2}}\right)+\left(\frac{1+i\sqrt 3}{2}\right)f\left(\sqrt{\frac{1-i\sqrt 3}{2}}\right)$$ Where $\displaystyle{f(a)=\int_0^{\infty} \frac{\tan^{-1}(x^2)}{x^2+a^2}=\frac{\pi}{2a}\left(\tan^{-1}(\sqrt{2}a+1)+\tan^{-1}(\sqrt{2}a-1)-\tan^{-1}(a^2)\right)},\,$ but I don't see how to simplify further.

I also tried the "straight forward" way, by employing Feynman's trick to the following integral: $$I(b)=\int_0^\infty \frac{\arctan(bx)^2}{x^4+x^2+1}dx\rightarrow \frac{d}{db}I(b)=\int_0^\infty \frac{2bx^2}{(x^4+x^2+1)(1+b^4x^4)}dx$$ $$=\frac{2b}{b^8-b^4+1}\int_0^\infty \frac{x^2}{x^4+x^2+1}dx-\frac{b^5}{b^8-b^4+1}\int_0^\infty \frac{dx}{x^2+x+1}+$$$$+\frac{2b^5}{b^8-b^4+1}\int_0^\infty\frac{dx}{1+b^4x^4}+\frac{b^9-b^5}{b^8-b^4+1}\int_0^\infty \frac{x^2}{1+b^4x^4}dx$$ $$=\frac{\pi}{\sqrt 3}\frac{b}{b^8-b^4+1}-\frac{2\pi}{3\sqrt 3}\frac{b^5}{b^8-b^4+1}+\frac{\pi}{\sqrt 2}\frac{b^4}{b^8-b^4+1}+\frac{\pi}{2\sqrt 2}\frac{b^6-b^2}{b^8-b^4+1}$$ Now since $I(0)=0$ we have: $ \displaystyle{I=I(1)-I(0)=\int_0^1 \left(\frac{d}{db}I(b)\right)db}$

Integrating the first two parts is okay-ish, but for the last two I have no idea on how to proceed, also it seems that only elementary constants appear thus I believe the integral can be approached in a nicer way. I would love to get some help, if it's possible without using residues since I am not great there.

$\endgroup$
  • 3
    $\begingroup$ ISC yields $$ J = \pi\left( \log(1+\sqrt{2}) - \frac{1}{2}\log(2+\sqrt{3}) \right).$$ $\endgroup$ – Sangchul Lee Nov 3 '18 at 22:00
  • $\begingroup$ @SangchulLee, quite nice. I believe with some effort this form can be straightforwardly obtained from the OP's value by separating real and imaginary parts in all the functions $\endgroup$ – Yuriy S Nov 3 '18 at 22:07
  • 1
    $\begingroup$ I believe it is way easier to invoke Feynman's trick. By writing $\arctan(x^2)$ as $\int_{0}^{1}\frac{x^2}{1+a^2 x^4}\,da$ and switching the the order of integration, then mapping $a$ into $u^2$, the evaluation of the original integral boils down to the evaluation of the integral of a rational function, which can be performed through partial fraction decomposition. $\endgroup$ – Jack D'Aurizio Nov 3 '18 at 22:43
  • $\begingroup$ @JackD'Aurizio not like I did when I considered $I(b)$? $\endgroup$ – Zacky Nov 3 '18 at 22:49
  • 1
    $\begingroup$ Sure, and since $b^8-b^4+1 = \Phi_{24}(b)$ you only need to compute residues at the $24$-th primitive roots of unity. $\endgroup$ – Jack D'Aurizio Nov 3 '18 at 22:55
7
$\begingroup$

Complete answer now!$$I=\int_0^\infty \frac{{\arctan(x^2)}}{x^4+x^2+1}dx {\overset{x=\frac1{t}}=} \int_0^\infty \frac{\arctan\left(\frac{1}{t^2}\right)}{\frac{1}{t^4}+\frac{1}{t^2}+1}\frac{dt}{t^2}\overset{t=x}=\int_0^\infty \frac{{x^2\left(\frac{\pi}{2}-\arctan(x^2)\right)}}{x^4+x^2+1}dx $$ Now if we add the result with the original integral $I$ we get: $$2I=\frac{\pi}{2}\int_0^\infty \frac{x^2}{x^4+x^2+1}dx+\int_0^\infty \frac{(1-x^2)\arctan(x^2)}{x^4+x^2+1}dx$$ $$\Rightarrow I = \frac12 \cdot \frac{\pi}{2}\cdot \frac{\pi}{2\sqrt 3}-\frac12 \int_0^\infty \frac{(x^2-1)\arctan(x^2)}{x^4+x^2+1}dx=\frac{\pi^2}{8\sqrt 3} -\frac12 J$$


Now in order to calculate $J\,$ we start by performing IBP: $$J=\int_0^\infty \frac{(x^2-1)\arctan\left(x^2\right)}{x^4+x^2+1}dx =\int_0^\infty \arctan(x^2) \left(\frac12 \ln\left(\frac{x^2-x+1}{x^2+x+1}\right)\right)'dx=$$ $$=\underbrace{\frac{1}{2}\ln\left(\frac{x^2-x+1}{x^2+x+1}\right)\arctan(x^2)\bigg|_0^\infty}_{=0}+\int_0^\infty \frac{x}{1+x^4}\ln\left(\frac{x^2+x+1}{x^2-x+1}\right)dx$$ Substituting $x=\tan\left(t\right)$ and doing some simplifications yields: $$J=\int_0^\frac{\pi}{2} \frac{2\sin (2t)}{3+\cos(4t)}\ln\left(\frac{2+\sin (2t)}{2-\sin (2t)}\right)dt\overset{2t=x}=\int_0^\pi \frac{\sin x}{3+\cos(2x)}\ln\left(\frac{2+\sin x}{2-\sin x}\right)dx=$$ $$=2\int_0^\frac{\pi}{2}\frac{\sin x}{3+\cos(2x)}\ln\left(\frac{2+\sin x}{2-\sin x}\right)dx=\int_0^\frac{\pi}{2}\frac{\cos x}{1+\sin^2 x}\ln\left(\frac{2+\cos x}{2-\cos x}\right)dx =$$ $$=\frac12\int_0^\pi \frac{\cos x}{1+\sin^2 x}\ln\left(\frac{2+\cos x}{2-\cos x}\right)dx\overset{\large{\tan\left(\frac{x}{2}\right)=t}}=\int_0^\infty \frac{1-t^2}{t^4+6t^2+1}\ln\left(\frac{\color{blue}{t^2+3}}{\color{red}{3t^2+1}}\right)dt$$

Splitting the integral into two parts followed by the substitution $\,\displaystyle{t=\frac{1}{x}}\,$ in the second part gives: $$\int_0^\infty \frac{1-t^2}{t^4+6t^2+1}\ln(\color{red}{3t^2+1})dt =\int_0^\infty \frac{x^2-1}{x^4+6x^2+1}\ln\left(\color{red}{\frac{x^2+3}{x^2}}\right)dx$$ $$\Rightarrow J=\int_0^\infty \frac{1-x^2}{x^4+6x^2+1} \ln(\color{blue}{1+x^3})dx - \int_0^\infty \frac{1-x^2}{x^4+6x^2+1} {\left(\ln(\color{red}{x^2})-\ln(\color{red}{x^2+3})\right)}dx=$$ $$=2\int_0^\infty \frac{1-x^2}{x^4+6x^2+1}\ln\left(\color{purple}{\frac{x^2+3}{x}}\right)dx=2\int_0^\infty \left(\frac12\arctan\left(\frac{2x}{1+x^2}\right)\right)'\ln\left(\frac{x^2+3}{x}\right)dx=$$ $$=\underbrace{\arctan\left(\frac{2x}{1+x^2}\right)\ln\left(\frac{x^2+3}{x}\right)\bigg|_0^\infty}_{=0}-\int_0^\infty \arctan\left(\frac{2x}{1+x^2}\right)\left(\frac{2x}{x^2+3}-\frac{1}{x}\right)dx$$ $$\Rightarrow J=\int_0^\infty \arctan\left(\frac{2x}{1+x^2}\right)\frac{dx}{x}-\int_0^\infty \arctan\left(\frac{2x}{1+x^2}\right) \frac{2x}{x^2+3}dx=J_1-J_2$$


$$J_1=\int_0^\infty \arctan\left(\frac{2x}{1+x^2}\right)\frac{dx}{x}\overset{\large{x=\tan\left(\frac{t}{2}\right)}}=\int_0^\pi \frac{\arctan( \sin t)}{\sin t} dt\overset{t=x}=2\int_0^\frac{\pi}{2} \frac{\arctan( \sin x)}{\sin x} dx$$ In general, we have the following relation: $$\frac{\arctan x}{x}=\int_0^1 \frac{dy}{1+(xy)^2} \Rightarrow \color{red}{\frac{\arctan(\sin x)}{\sin x}=\int_0^1 \frac{dy}{1+(\sin^2 x )y^2}}$$ $$J_1 = 2\color{blue}{\int_{0}^{\frac{\pi}{2}}} \color{red}{\frac{\arctan\left(\sin x\right)}{\sin x}}\color{blue}{dx}=2\color{blue}{\int_0^\frac{\pi}{2}}\color{red}{\int_0^1 \frac{dy}{1+(\sin^2 x )y^2}}\color{blue}{dx}=2\color{red}{\int_0^1} \color{blue}{\int_0^\frac{\pi}{2}}\color{purple}{\frac{1}{1+(\sin^2 x )y^2}}\color{blue}{dx}\color{red}{dy}$$ $$=2\int_0^1 \frac{\arctan\left(\sqrt{1+y^2}\cdot\tan(x)\right) }{\sqrt{1+y^2}} \bigg|_0^\frac{\pi}{2}=\pi\int_0^1 \frac{dy}{\sqrt{1+y^2}}=\boxed{\pi\ln\left(1+\sqrt 2\right)}$$


In order to evaluate $J_2$ we return the integral before was integrated by parts. $$J_2=2\int_0^\infty \arctan\left(\frac{2 x} {x^2 +1}\right)\frac{x}{x^2 +3}dx=2\int_0^{\infty}\frac{(x^2-1)\ln(x^2+3)}{x^4+6x^2+1} dx=$$ $$=(\sqrt 2+1)\int_0^{\infty} \frac{\ln(x^2+3)}{x^2+\left(\sqrt 2+1\right)^2} \ dx - (\sqrt 2-1)\int_0^{\infty} \frac{\ln(x^2+3)}{x^2+\left(\sqrt 2-1\right)^2} dx$$ Using the following identity that is valid for $a\ge 0, b>0$:$$\int_0^{\infty} \frac{\ln(x^2+a^2)}{x^2+b^2} \ dx = \frac{\pi}{b}\ln(a+b)$$ $$\Rightarrow J_2=\pi\ln\left(\frac{\sqrt{3}+\sqrt{2}+1}{\sqrt{3}+\sqrt{2}-1}\right)=\boxed{\frac{\pi} {2}\ln(2+\sqrt 3)}$$ So we found that:$$J=\boxed{\pi \ln(1+\sqrt 2) - \frac{\pi} {2} \ln(2+\sqrt 3)}\Rightarrow I= \large\boxed{\frac{\pi^2} {8 \sqrt 3}+\frac{\pi}{4}\ln(2+\sqrt 3)-\frac{\pi}{2} \ln(1+\sqrt 2)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.